Photoimmunotheranostic targeting of CSPG4-positive melanoma cells using SNAP-tag technology - Malindi, Zaria (Department of Integrative Biomedical Sciences (IBMS), 2020)
Melanoma is one of the most aggressive and inherently resistant cancers and the most dangerous skin cancer. While it accounts for fewer than 5% of skin cancer cases, 80% of skin cancer related deaths are attributed to melanoma. While resection remains the gold standard for melanoma treatment, surgery is only effective in providing local control of the disease if the cancer is detected in the early stages. Once melanoma enters the later stages, and particularly in the metastatic phase, recurrence is probable, and no adequate treatment exists. Previous work in this group has shown that photodynamic therapy (PDT) presents an opportunity to induce cell death in melanoma cells through the production of ROS and singlet oxygen at doses high enough to overwhelm the resistance mechanisms of the cancer. In this study, we investigated the use of recombinant SNAP-tag-based antibody fusion proteins as a means of delivering phototoxic molecules directly to cancer cells expressing the CSPG4 and PD-L1 cell surface receptors. SNAP-tag is an engineered version of the human DNA repair enzyme O6-alkylguanine-DNA alkyltransferase. It reacts autocatalytically and in a strictly 1:1 coupling chemistry with substrates that have been modified with benzylguanine (BG). Through genetic fusion of this self-labelling protein with a tumour targeting antibody, we developed a recombinant immunoconjugate able to carry BG-modified photosensitizers to selectively target and eliminate malignant melanoma cells. Conjugation of the SNAP-tag fusion protein with the fluorescent dye Alex Fluor 488 showed that anti-CSPG4-SNAP binds specifically to melanoma cells expressing the CSPG4 surface antigen. Binding was tested across a range of cell lines presenting melanoma in its radial and vertical growth phases, in the metastatic growth phase, in its chemoresistant form, and in both its pigmented and unpigmented forms. This binding data thus confirms CSPG4 as a suitable targeted for this treatment strategy. Conjugation of the fusion protein with the BGmodified photosensitizer IRDye 700DX (IR700) has produced no phototoxicity as of yet. In light of the convincing binding analysis, it is concluded that inefficient solubilization of the lyophilized product resulted in inadequate conjugation of BG-IR700 with SNAP-tag. Nonetheless, steps have been planned to resolve the problem in future ongoing work on this project, and we remain confident in the applicability of this technology. The results for the PD-L1 fusion protein were inconclusive. In summary, SNAP-tag technology offers a simple and efficient method for immunofluorescent detection of cancerous cells. These fusions proteins are versatile as they 1) can contain any antibody targeting a tumour-associated or tumour-specific antigen of choice and 2) can be endowed with a wide variety of substrates, as long as the latter contains the BG moiety.